Peran DKUPP Kabupaten Probolinggo pada Perizinan Industri Kecil Menengah Produk Roti dan Kue di Kabupaten Probolinggo - Popy Amilia; Imam Syafi'i; Ahmad Fajri (Masyarakat Ekonomi Syariah Bogor, 2024)
DKUPP (Department of Cooperatives, Micro Enterprises, Trade and Industry of Probolinggo Regency), especially in the industrial sector, has a role in licensing IKM (Small and Medium Industries) for bread and cake products. The industrial sector is one of the fields that carries out production guidance and development, industrial business development, as well as licensing control and supervision. The industrial sector has a role in registering permits or legality and also helping entrepreneurs who experience difficulties in making product packaging. The aim of the research is to determine the role of DKUPP in licensing SMEs for bread and cake products, the role of packaging houses in SMEs, obstacles to registering permits, the development of SMEs after obtaining a permit or the legality of the business. Qualitative research method with a descriptive approach, using sampling techniques based on the characteristics of the research object. Data collection techniques include interviews and documentation. The research results show that the role of DKUPP in IKM licensing helps entrepreneurs register business legality letters to facilitate product marketing and product safety. The role of packaging houses for SMEs or entrepreneurs is to assist in making packaging and assist with consultations regarding product packaging. Obstacles to licensing include a lack of understanding of licensing, the development of SMEs after having a permit or business legality, namely the large number of entrepreneurs, especially bread and cake products, who are able to market their products outside the city and reach large shops.